2020
DOI: 10.1021/acsnano.0c08068
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled and Near-Infrared-Phototaxic Photosynthetic Bacteria as Photothermal Agents for Hypoxia-Targeted Cancer Therapy

Abstract: Hypoxia can increase the resistance of tumor cells to radiotherapy and chemotherapy. However, the dense extracellular matrix, high interstitial fluid pressure, and irregular blood supply often serve as physical barriers to inhibit penetration of drugs or nanodrugs across tumor blood microvessels into hypoxic regions. Therefore, it is of great significance and highly desirable to improve the efficiency of hypoxia-targeted therapy. In this work, living photosynthetic bacteria (PSB) are utilized as hypoxia-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 46 publications
2
48
0
2
Order By: Relevance
“…More importantly, the calculated photothermal conversion efficiency of HPDC NPs was 28.9% (Figs. 1 J and K), which was even better than that of many photothermal conversion nanoagents, including HCuSNPs (23.8%) [ 51 ], AIPH@Nb2C@mSiO2 NPs (27.03%) [ 52 ], and living photosynthetic bacteria (PSB) (27.3%) [ 53 ]. These results indicated that HPDC NPs could be used as a potential photothermal agent for future photothermal therapy attributing to its prominent photothermal conversion performance.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the calculated photothermal conversion efficiency of HPDC NPs was 28.9% (Figs. 1 J and K), which was even better than that of many photothermal conversion nanoagents, including HCuSNPs (23.8%) [ 51 ], AIPH@Nb2C@mSiO2 NPs (27.03%) [ 52 ], and living photosynthetic bacteria (PSB) (27.3%) [ 53 ]. These results indicated that HPDC NPs could be used as a potential photothermal agent for future photothermal therapy attributing to its prominent photothermal conversion performance.…”
Section: Resultsmentioning
confidence: 99%
“…目 前, 几种乏氧激活前药已经进入临床试验, 如Evofosfamide(TH-302)、替拉扎明(TPZ)和班诺蒽醌(AQ4N) 等 [35] . 然而, 直接使用小分子药物仍存在一些问题, 如 药物溶解度差、血半衰期短等 [36] . 利用纳米载体进行 药物递送可以在一定程度上克服上述问题 [37] .…”
Section: 乏氧激活型纳米药物unclassified
“…而CSCs又是造成肿 瘤发生、转移和耐药的关键因素 [42] . 基于此, 本课题 组 [34] 设计了基于介孔二氧化硅的多级靶向纳米药物 (2) 构建具有抗氧化功能的纳米药物: 肿瘤细胞内 高水平的活性氧(ROS)会导致脯氨酰羟化酶(PHD)失 活, 并进一步阻断乏氧诱导因子-1(HIF-1)的降解过程, 构建具有抗氧化功能的纳米药物, 通过降低肿瘤组织 图 3 (a) 多级靶向药物递送纳米系统的构建及其靶向治疗肿瘤干细胞的示意图 [34] ; (b) 在有或无AFM作用下, CD133/TAT-Fe 3 O 4 @mSiO 2 靶向乳腺癌干细胞的细胞核的共聚焦激光扫描结果 [34] ; (c) 经不同实验组处理后, 乳腺癌干细胞肿瘤球生存能力 的代表性图像 [34] ; (d) 不同组实验组处理后, 乳腺癌干细胞生存能力的流式细胞仪检测结果 [34] (网络版彩图) 图 4 (a) 具有自我推进和近红外趋光能力的光合细菌用作光热剂以消除乏氧肿瘤的示意图 [36] ; (b) PSB的紫外线-近红外吸收 光谱(上), 以及PSB(10 9 CFU/mL)在不同功率强度下的升温曲线(下) [36] ; (c) 注射48 h后, 小鼠主要器官的离体荧光成像及肿瘤 组织远端荧光强度的定量分析 [36] (网络版彩图)…”
Section: 乏氧激活型纳米药物unclassified
See 1 more Smart Citation
“…On the other aspect, bacteria recently have achieved encouraging outcomes in cancer therapy [29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%